Multiculturalism and Rights: a conceptual approach (Management & Public Policies Journal, 2020)
The discussion about multiculturalism and multicultural public policies has been the object of controversies and great conceptual divergence. The present text updates the debate about multiculturalism, points out the differences between multicultural countries and countries that, even being multicultural, do not admit policies focused on multiculturalism. I discuss here some concepts and ideas that can help to understand different aspects of what is understood by multiculturalism from the theories of justice, as well as the different forms of normative treatment to the demands of social groups in contemporary societies.